TRANSMUTED ARCSINE DISTRIBUTION PROPERTIES AND APPLICATION - Bleed, Salma Omar; Abdelali, Arwa Elsunousi Ali (International Journal of Research -GRANTHAALAYAH, 2018)
The distribution of ArcSine will be developed to another new distribution using the Quadratic Rank Transmutation (QRT) method proposed by Shaw and Buckley (2007). The new distribution will be called the Transmuted ArcSine distribution, some of its mathematical characteristics such as variance, expectation, residual function, risk function, moments, moment generating function and characteristic function will be presented. The model parameters will be estimated by the maximum likelihood method. Finally, two real data sets are analyzed to illustrates the usefulness of the TAS distribution.